(untitled) (Tidsskrift for Praktisk Teologi, 2023)
Given a lack of research on the relations between popular culture and religious socialisation, the article examines confirmation teachers’ use of film within the Church of Norway. What characterises confirmation teachers’ reflections and justifications for the use of film? The data consists of 6 qualitative interviews with confirmation teachers who lead groups where films are deliberately used as tool within teaching. Three dominant strategies emerge: (1) film as community and experience, (2) film pointing to something else, either as actualizations or metaphors, and (3) film building bridges between the lifeworld of the confirmands and the church. Based on H. Richard Niebuhr’s typology of the relationship between Christ and Culture, article discusses the findings in the relationship between theology, popular culture and religious socialisation.